Firearm Injuries: Surviving Gun Violence in Ecuador - Álvarez Velasco, Carla M. (2020)
This article discusses non-lethal armed violence in Ecuador. Its main objective is to show the dynamics of armed violence to make visible its impacts and to encour-age the adoption of policies to reduce it. This paper also throws a light on the vic-tims’  needs  and  the  importance  of  promoting  a  culture  of  peace.  This  work  us-es Johan Galtung’s theoretical perspective of direct and structural violence. This approach employs a qualitative methodology that uses the interview as the main tool to gather information on the causes and consequences of this specific kind of  violence.  This  article  analyses  the  results  of  interviews  held  with  people  living  in Quito and Guayaquil. The cases show that in the country, as in the rest of the world,  poor  people  are  the  most  affected  by  non-lethal  armed  violence.  It  also  shows that victims have restricted access to medical, psychological, security care, and  justice.  Finally,  this  paper  highlights  the  importance  of  adopting  measures  that could reduce the impact of armed violence and conducting further research on this reality to transform it.